Terreur, roes en ordes: Die monnik as blywende simbool van erns in die filosofie - Beukes, Johann (HTS teologiese studies, 2005)
Terror, frenzy and orders: The monk as persistent symbol of ardour in philosophyIt is argued that postmodern epistemology, in its 21st century guise, is exhausted, with little to offer post-Baudrillard. In thematic conjunction with the critiques of Fredric Jameson, Christopher Norris and Jürgen Habermas, the author depicts 21st century postmodernism as a “frenzied party”, where philosophy’s historical and characteristic ardour for truth and analysis has been dissolved in favour of a mockery of some of the most profound ideas of Western civilization, such as truth, beauty and justice. The logical consequences of this frenzied epistemology are described as socially devastating, especially within the context of systematic terror, which is described as the predominant social marker of the first years of the 21st century. The author, in reaction both to terror and “epistemological frenzy”, attempts to rehabilitate philosophical ardour and a zeal for truth by linking up with the historical persona of “the monk”, arguing that our times demand a more studied, retracted and meditative approach to philosophy. Our dreadful times demand a new ardour and sobriety from philosophers.